Caracterização do retrotransposon 412 em espécies do gênero Drosophila - Santos, Leandro Amancio dos (2013)
Transposable Elements (TEs) are DNA sequences with ability to mobilize itself either into the host genome or horizontally between different genomes. Because their dynamic in the host genomes to them is atributed great evolutionary importance by act as sources of genetic recombination and novelties. The understanding of the issues about the dynamics, diversity and evolution of TEs has been intensively studied in the genome of Drosophila, because it is an efficient model for genetic studies. The 412 TE, was originally characterized in the Drosophila melanogaster genome. It belongs to Ty3 superfamily (retrotransposon) and have been detected in several species of the Genus Drosophila (by hybridizations techniques), where it presents a high degree of polymorphic copies. Thus, to investigate the nature of this diversity can be an efficient way for a better understanding of the evolutionary history of this TE in Drosophila's genome as well as to help the comprehension of the phylogeny of this genus itself. In order to detect the presence of this TE in different species of Drosophila Genus, to characterize its possible copies found and to compare their similarity, we performed a PCR amplification using primers for 412 from D. melanogaster in 11 species of the subgenus Drosophila, nine species of the subgenus Sophophora and one specie of the subgenus Dorsilopha. Products of this amplification were hybridized by Southern blot using as a probe the intern fragment of 412 TE from D. melanogaster. The amplified fragments were purified for subsequent sequencing and analysis. Among the 21 investigated species, 14 presented amplifications for 412 TE, however, just in D. funebris, D. buzzatii, D. kikkawai and D. simulans, besides D. melanogaster, their presence was confirmed by hybridization. We observed high variation on the detected patterns, which suggests differences between the copies amplified on these analyzed species and divergences even among species of a same ix group. Further sequencing and analyses of the sequences will allow to evaluate the similarity between this TE copies in the analyzed genomes. Only the fragment isolated from D. simulans (White) resulted in a sequence with quality for analysis. This sequence was analyzed in silico by BLAST tool and showed high homology with the canonical element of D. melanogaster (89%) and other regions of the genome of D. melanogaster and D. sechelia. Our data reinforce the available knowledge about the wide distribution of TE among species of the genus Drosophila, now under a molecular approach.